Question about Mathsoft Solving and Optimization Extension Pack III (46513) for PC

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

Nouns that name common (non personal) objects. Cow, house, cat are common nouns. Peter and Paul are personal nouns.Common nouns are not capitalized.

Feb 10, 2015 | Computers & Internet

let c = cory's age now
let s = her sisters age now

cory's age now = sisters age + 6 years

=> c = s + 6

4 years ago, cory was 4 years younger ( i.e. c-4) and her sister was 4 years younger (s- 4)

4 years ago cory was 4 times older than her sister

=> c - 4 = 4*(s-4)

We can simplify this to c = 4s - 16 +4 c = 4s - 12

We can then use simultaneous equations to solve the two equations

(i) c = s + 6 (ii) c = 4s - 12

If we multiply both sides of equation (i) by 4 we get (iii) 4c = 4s + 24

We can then subtract equation (ii) from equation (iii) to eliminate the '4s' term => ( 4c = 4s + 24 ) - (c = 4s - 12) => 4c - c = 4s +24 - 4s +12 => 3c = 4s - 4s +36 => 3c = 36 => c = 36/3 => c = 12 => Cory's age now = 12

__For clarity:__
Her sister's age now is of course 6
4 years ago Cory would of been 8 and her sister would of been 2

I hope this helps and good luck! If you have more questions - ask away!

Please take the time to rate this answer

Many Thanks Don.

cory's age now = sisters age + 6 years

=> c = s + 6

4 years ago, cory was 4 years younger ( i.e. c-4) and her sister was 4 years younger (s- 4)

4 years ago cory was 4 times older than her sister

=> c - 4 = 4*(s-4)

We can simplify this to c = 4s - 16 +4 c = 4s - 12

We can then use simultaneous equations to solve the two equations

(i) c = s + 6 (ii) c = 4s - 12

If we multiply both sides of equation (i) by 4 we get (iii) 4c = 4s + 24

We can then subtract equation (ii) from equation (iii) to eliminate the '4s' term => ( 4c = 4s + 24 ) - (c = 4s - 12) => 4c - c = 4s +24 - 4s +12 => 3c = 4s - 4s +36 => 3c = 36 => c = 36/3 => c = 12 => Cory's age now = 12

I hope this helps and good luck! If you have more questions - ask away!

Please take the time to rate this answer

Many Thanks Don.

Sep 13, 2011 | Sunburst My Mathematical Life Single...

Hi

Never.

Even a February 29th Leap Year birthday only rings their ages within 11-12 years of each other.

Never.

Even a February 29th Leap Year birthday only rings their ages within 11-12 years of each other.

Aug 27, 2011 | TOPICS Entertainment College Pro...

Twenty-two billion, four hundred fifty-five million, seven hundred eighty six thousand and four.

Jun 13, 2011 | Computers & Internet

Jamie = x

Luiz = x+4

Ramon = x+7

3x+11=29

3x=18

x=6

Jamie = 6 , Luiz = 6+4 = 10 , Ramon = 6+3 = 13

Luiz = x+4

Ramon = x+7

3x+11=29

3x=18

x=6

Jamie = 6 , Luiz = 6+4 = 10 , Ramon = 6+3 = 13

Oct 13, 2010 | MathRescue Word Problems Of Algebra Lite

(D=Dad's age, and S=Son's age)

D=S+20 (Dad is 20 years older than Son)

D+10 = 2xS (In ten years Dad will be twice Son's current age)

therefore (by substitution):

S+20+10 = 2xS

S+30 = 2S

2S = S+30

2S-S = 30 (subtract S from both sides)

D = S+20

D = 30+20

In ten years, Dad will be 60, which is twice Son's current age of 30.

Please ask for -Gort.

Aug 27, 2010 | Mathsoft Solving and Optimization...

Allan is 19 and Roy is 13.

Solution:

First we have 2 variables, their ages: I used Allan = x & Roy = y

Equation 1: X - 4 = 2*(Y-4) - 3

We can ignore the 5 years in the second part of the statement. Allan will always be 6 years older than Roy whether it be 5 years from now or ten years form now.

Equation 2: X = Y + 6

Substitute Y + 6 for X in equation 1:

X - 4 = 2*(Y-4) - 3 becomes Y + 6 - 4 = 2*(Y-4) - 3

That simplifies to Y + 2 = 2Y - 8 - 3

Rewrite it again: Y + 2 = 2Y - 11

Add 11 to both sides: Y + 13 = 2Y

Subtract Y from both sides: 13 = Y

Now plug 13 in for y in Equation 2

X = Y + 6

X = 13 + 6

X = 19

Solution:

First we have 2 variables, their ages: I used Allan = x & Roy = y

Equation 1: X - 4 = 2*(Y-4) - 3

We can ignore the 5 years in the second part of the statement. Allan will always be 6 years older than Roy whether it be 5 years from now or ten years form now.

Equation 2: X = Y + 6

Substitute Y + 6 for X in equation 1:

X - 4 = 2*(Y-4) - 3 becomes Y + 6 - 4 = 2*(Y-4) - 3

That simplifies to Y + 2 = 2Y - 8 - 3

Rewrite it again: Y + 2 = 2Y - 11

Add 11 to both sides: Y + 13 = 2Y

Subtract Y from both sides: 13 = Y

Now plug 13 in for y in Equation 2

X = Y + 6

X = 13 + 6

X = 19

Oct 08, 2009 | Vivendi Math Blaster Algebra (03763) for...

The two numbers 3 and 24

3 multiplied by 24 =72

24 divided by 3 =8

Enjoy, and thanks for choosing Fixya!

3 multiplied by 24 =72

24 divided by 3 =8

Enjoy, and thanks for choosing Fixya!

Mar 20, 2009 | M2K Garfield: It's All About Math Math...

Edwin is 14. Ruel is 7.

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

Dec 11, 2008 | Computers & Internet

Since you have the answer, the easiest way to work with this is to work with real numbers and break it down. What are the knowns?

Rose + 25 = Dad

10 + 25 = 35 (today)

5 years ago, Dad (then 30) was 2x old as Rose will be 5 years from now (+5), or (30/2) -5 = 10

You can also put this into formulas

Rose + 25 = Dad

Dad - 5 = 2 * (Rose + 5)

So, if Dad = Rose + 25, you can substitute one for the other in the 2nd formula, like so:

(Rose + 25) - 5 = 2 * (Rose + 5)

Rose + 20 = 2 * (Rose + 5)

Now, you can solve for Rose and eventually come up with 10

I hope this helps.

Rose + 25 = Dad

10 + 25 = 35 (today)

5 years ago, Dad (then 30) was 2x old as Rose will be 5 years from now (+5), or (30/2) -5 = 10

You can also put this into formulas

Rose + 25 = Dad

Dad - 5 = 2 * (Rose + 5)

So, if Dad = Rose + 25, you can substitute one for the other in the 2nd formula, like so:

(Rose + 25) - 5 = 2 * (Rose + 5)

Rose + 20 = 2 * (Rose + 5)

Now, you can solve for Rose and eventually come up with 10

I hope this helps.

Jul 20, 2008 | Computers & Internet

278 people viewed this question

Usually answered in minutes!

×